2018
DOI: 10.1080/07448481.2018.1462818
|View full text |Cite
|
Sign up to set email alerts
|

Who is willing to come back? College students' willingness to seek help after using campus mental health services

Abstract: The predictors for willingness to use services in the future were consistent with the existing literature related to initial use. Colleges and universities need to consider factors that influence openness to MH services after a previous experience in addition to initiating care. Implications for college MH professionals are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…When considering access healthcare in this sense, it is important to note that patients must actually be seeking care. For example, individuals have access to mental healthcare if there is available care in their area (Alakeson et al, 2010) and they have knowledge about where to seek access (e.g., ability of college students to find mental healthcare services on campus; Oswalt et al, 2019). In other instances, individuals may lack the strength or capacity to access mental health services (e.g., seeking mental health services following psychological distress/trauma such as the death of a loved one; Lichtenthal et al, 2015).…”
Section: Concept Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…When considering access healthcare in this sense, it is important to note that patients must actually be seeking care. For example, individuals have access to mental healthcare if there is available care in their area (Alakeson et al, 2010) and they have knowledge about where to seek access (e.g., ability of college students to find mental healthcare services on campus; Oswalt et al, 2019). In other instances, individuals may lack the strength or capacity to access mental health services (e.g., seeking mental health services following psychological distress/trauma such as the death of a loved one; Lichtenthal et al, 2015).…”
Section: Concept Analysismentioning
confidence: 99%
“…Access to mental healthcare involves three central attributes that emerged from the literature: connectedness, clinical management, and healthcare delivery (Table 1). Connectedness refers to connectivity (e.g., through technology), geographical location (travel time/distance for specific mental health services; White Hughto et al, 2016), feeling of belonging to a particular group, or just the state of being linked to services (Chavez et al, 2018; Oswalt et al, 2019; Purtle et al, 2016; Ramsay et al, 2012; Rintell et al, 2012). For example, lack of support (from family, caregivers, friends; Ramsay et al, 2012), social services (case managers, supportive housing, early intervention programs), and resources (lack of mental health clinicians, lack of available beds) can all encompass an individual’s lack of connectedness when describing access to mental healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…When considering the evidence, however, all classes thought they would be more likely to remain in services that students who had experienced mental health problems found to be helpful. Indeed, in a study of 12,501 undergraduate students, 90% reported they would use mental health services again (Oswalt et al, 2019). Research evidence and the recommendations of mental health professionals, in contrast, exerted relatively little influence on the decision to remain in treatment.…”
Section: Implications For the Design Of Campus Mental Health Servicesmentioning
confidence: 99%